2020
DOI: 10.1111/evj.13370
|View full text |Cite
|
Sign up to set email alerts
|

Variation in GPS and accelerometer recorded velocity and stride parameters of galloping Thoroughbred horses

Abstract: Background With each stride, galloping horses generate large skeletal loads which influence bone physiology, and may contribute to musculoskeletal injury. Horse speed and stride characteristics are related, but the usefulness of using horse speed and distance travelled as a proxy for stride characteristics is unknown. Objectives We aimed to determine stride characteristics, their variance and their relationship with speed in horses performing maximally. Study design Retrospective cross‐sectional analysis of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Scientific inquiry into the gaits of extinct vertebrates has increased exponentially over the past few decades. Extensive investigations have been undertaken on the gaits of dinosaurs (Alexander, 1976;Thulborn, 1982Thulborn, , 1989Mazzetta and Blanco, 2001;Henderson, 2006;Stevens et al, 2016;Bordy et al, 2020), camels (Alf, 1966;Webb, 1972;Sarjeant and Reynolds, 1999;McNeil et al, 2007;Thompson et al, 2007;Cabral-Perdomo et al, 2018), and horses (Renders, 1984a, b;Kienapfel et al, 2014), among other vertebrates. Such studies have compared cycle (stride) length, speed, and footprint patterns of living species with fossilized trackways in order to elucidate the gaits of extinct vertebrate species.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific inquiry into the gaits of extinct vertebrates has increased exponentially over the past few decades. Extensive investigations have been undertaken on the gaits of dinosaurs (Alexander, 1976;Thulborn, 1982Thulborn, , 1989Mazzetta and Blanco, 2001;Henderson, 2006;Stevens et al, 2016;Bordy et al, 2020), camels (Alf, 1966;Webb, 1972;Sarjeant and Reynolds, 1999;McNeil et al, 2007;Thompson et al, 2007;Cabral-Perdomo et al, 2018), and horses (Renders, 1984a, b;Kienapfel et al, 2014), among other vertebrates. Such studies have compared cycle (stride) length, speed, and footprint patterns of living species with fossilized trackways in order to elucidate the gaits of extinct vertebrate species.…”
Section: Discussionmentioning
confidence: 99%
“…With advancement in inertial sensor technology, objective assessment of faster gaits is possible, but changes in gait in response to developing injury may only be apparent at extreme exertion. We have shown that there was substantial inter‐horse variation in racehorse stride characteristics with speed predicting half or less of this variation 15 . Therefore, simply comparing stride characteristics between horses is unlikely to predict injury risk.…”
Section: Introductionmentioning
confidence: 93%
“…Erroneous stride characteristic values were identified and excluded, including where the horse was pulled up, lost a rider, fell, or was injured or disqualified. Information about the cleaning and processing of the StrideMASTER dataset are detailed in Morrice-West et al 15 Table S1 details the variables existing in the merged dataset as well as the variables generated or transformed for analysis (i.e. cumulative and percentage variables) that may act as confounders or effect modifiers.…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations